Pengaruh FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN JASA TRANSPORTASI GOJEK DI MAGELANG - Nugroho, Wahid Putro (Universitas Muhammadiyah Magelang, 2019)
Technological progress is increasingly felt by all circles, such as product services (Go Box, Go Ride, Go Shop, and Go Food) produced by PT. Gojek Indonesia. But there are still consumers who complain about the quality of service from Gojek. This study aims to determine the effect of price and service quality on customer satisfaction provided by Gojek transportation services in Magelang. Data collection techniques in this study used random sampling techniques. The samples taken in this study were senior high school/vocational high school, college student, employee, and general public with 120 respondents. Analysis and testing of hypotheses using multiple linear regression. The results of this study state that Price and Service Quality have a positive effect on Customer Satisfaction.